INTERFERENSI BAHASA INDONESIA KE DALAM BAHASA INGGRIS PADA UJIAN TRANSLATION (NON-ENGLISH STUDY PROGRAM STUDENTS) - Haryani, Tutik (JURNAL SOCIOPOLITICO, 2019)
The research is aimed not only at discussing on an interference of Indonesian language into English language as shown in teranslation test for non English study program students, in this study is the students of FISIP Universitas PGRI Palangka Raya, but also at the description on the kinds of interference. In this study, there are 130 students of three classes which just 30 students takken as the sample. The method applied in this research is descriptive with distributional and similarity analysis. The data is collected from translation test for non English study program students, in this case the tudents of FISIP Universitas PGRI Palangka Raya 2015/2016 academic year. The results indicate that there are three kinds of interferences, namely: morphological, syntactic and semantic interferences. Morphology interference happens such as in verb form for the third person, plural form, and possessive. Syntactic interference includes the form of phrase and passive voice, parallelism, and the omission of to be and article. Semantic interference consists of addition and substitution.